2011
DOI: 10.1186/1477-7819-9-121
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of clinical significance of stem-cell related factors in renal cell cancer

Abstract: BackgroundC-MYC, LIN28, OCT4, KLF4, NANOG and SOX2 are stem cell related factors. We detected whether these factors express in renal cell carcinoma (RCC) tissues to study their correlations with the clinical and pathological characteristics.MethodsThe expressions of c-MYC, LIN28, SOX2, KLF4, OCT4 and NANOG in 30 RCC patients and 5 non-RCC patients were detected with quantitative real-time reverse transcription-PCR (qRT-PCR). The data were analyzed with Wilcoxon signed rank sum test and x2 test.ResultsIn RCC gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…However, the pattern of SOX2 expression and its correlation with clinical/ pathological outcomes of various cancers are highly controversial. In renal cell carcinoma and gastric cancer, the expression of SOX2 is reduced [31,32] , and the relationship between SOX2 expression and a favorable prognosis in non-small cell lung cancer, gastric cancer and renal cell carcinoma has been [31][32][33] . In contrast, other studies have related SOX2 expression to poor clinical outcomes, including cancer recurrence, and lymph node and distant metastasis in a variety of human malignancies [34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the pattern of SOX2 expression and its correlation with clinical/ pathological outcomes of various cancers are highly controversial. In renal cell carcinoma and gastric cancer, the expression of SOX2 is reduced [31,32] , and the relationship between SOX2 expression and a favorable prognosis in non-small cell lung cancer, gastric cancer and renal cell carcinoma has been [31][32][33] . In contrast, other studies have related SOX2 expression to poor clinical outcomes, including cancer recurrence, and lymph node and distant metastasis in a variety of human malignancies [34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…These reports suggest that the localization of KLF4 may differ between organs or according to the role of KLF4; however, it is notable that the decrease in KLF4 was associated with the progression of the cancer. With regard to the presence of KLF4 in tumor cells, various studies have revealed decreased KLF4 expression in patients with nasopharyngeal (22), colorectal (24), renal (25), lung (26), cervical (27) and breast cancer (28) who had poor prognosis. Based on these results, KLF4 was suggested to function as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous options can be used for reconstruction of the head and neck, including primary closure, skin grafts, pedicle flaps, healing by secondary intentions, and free flaps, all of these techniques have their limitations [2]. With the development of microsurgical techniques in recent years, free flaps, such as radial forearm flaps, latissimus dorsi flaps, and anterolateral thigh free flaps, have a tendency to predominate intraoral reconstruction.…”
Section: Introductionmentioning
confidence: 99%